TREND ANALYSIS OF CONFIRMED CASES OF STREPTOCOCCUS PNEUMONIAE FROM 2014 TO 2017 IN SELECT MUNICIPAL KANSAS COUNTIES - Ferrel, Colin Nathanial (My University, 2019)
Streptococcus pneumoniae, also known as pneumococcal disease, has been an extortionary burden on public health for well over a century and continues to affect high-risk groups, which includes the unvaccinated, children under the age of two, adults age sixty-five and older, and individuals with weakened immune systems or a history of smoking and/or asthma. Since 2015, Sedgwick County along with other select Kansas Counties have had a substantial increase in the number of S. pneumoniae cases. As a result, the county decided to uncover the possible cause(s) of the increased prevalence, if any of the population’s demographic might have been disproportionately affected and what the efficacy is of the available vaccines. After receiving the patient’s information from the included counties, the data was arranged into frequency and rate tables, followed by chi-square tables, to compare population estimates of the demographics for each county in Kansas (KS) to the study populations. The study populations were found to be representative of each of the Counties and KS overall. Calculations were then performed using R to compare the odds of mortality between the unvaccinated and vaccinated, the type of vaccine received and the county in which they reside. Lastly, a model containing the variables: age, race/ethnicity and county of residence was run to approximate a rate of diseases using the included variables. Unfortunately, due to a low study population, most of the findings were not significant. However, County of residence, year of initial diagnosis, vaccine type received, number of days hospitalized post-infection, and underlying medical conditions were found to be the best predictor of the patient’s odds of succumbing to S. pneumoniae.
Keywords: Streptococcus pneumoniae; epidemiology; Sedgwick County; s. pneumoniae